2023
DOI: 10.1126/sciimmunol.add5724
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine gland–resident memory CD8 + T cells use mechanosensing for tissue surveillance

Nora Ruef,
Jose Martínez Magdaleno,
Xenia Ficht
et al.

Abstract: Tissue-resident CD8 + T cells (T RM ) continuously scan peptide-MHC (pMHC) complexes in their organ of residence to intercept microbial invaders. Recent data showed that T RM lodged in exocrine glands scan tissue in the absence of any chemoattractant or adhesion receptor signaling, thus bypassing the requirement for canonical migration-promoting factors. The signals eliciting this noncanonical motility and its relevance for organ surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…It was recently shown that mechanical input leads to transcriptional changes in T cells [84][85][86] . Moreover, stiffness sensing by effector T cells is a critical driver of the differentiation of tissue resident memory T cells, and confinement-induced motility plays a role in antigen surveillance by T cells in the salivary gland 44,85 . Overall, defining the signaling axes which impact the ability of T cells to migrate through and establish residence in confined tissue environments may provide a therapeutic opportunity to modulate the migration to, and survival within, tissues where T cell surveillance is undesirable, for instance in autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that mechanical input leads to transcriptional changes in T cells [84][85][86] . Moreover, stiffness sensing by effector T cells is a critical driver of the differentiation of tissue resident memory T cells, and confinement-induced motility plays a role in antigen surveillance by T cells in the salivary gland 44,85 . Overall, defining the signaling axes which impact the ability of T cells to migrate through and establish residence in confined tissue environments may provide a therapeutic opportunity to modulate the migration to, and survival within, tissues where T cell surveillance is undesirable, for instance in autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…As the appearance of the central F-actin cloud was only seen under confinement, we next asked whether this mechanosensitive F-actin response would be modulated by the rigidity of confining agar. To address this, we titrated the percent agarose from 0.5 to 2% to increase the degree of mechanical load 44 . Indeed, the fluorescence intensity at the cell centroid of F-actin scaled with the percent agarose in WT T cells (Fig.…”
Section: Dock8 Is Necessary For a Mechanoresponsive Integrin-independ...mentioning
confidence: 99%